2000
DOI: 10.1139/z99-226
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal pattern and effective population size of the beaver

Abstract: The dispersal pattern of the beaver (Castor canadensis) was studied by intensive livetrapping, tagging, and observation in Allegany State Park and its vicinity in New York from 1984 to 1996. The majority (74%) of dispersing beavers (n = 46) initiated dispersal in a downstream direction after spring ice-out. Females dispersed significantly farther away from their natal colonies than males (10.15 ± 2.42 (SE) km vs. 3.49 ± 0.86 km). Movements to neighboring sites were common (16 of 46 dispersers), indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 32 publications
3
26
1
Order By: Relevance
“…This is not surprising as other studies in the native range found juveniles dispersed close to their natal colonies (Sun et al 2000;VanDeelen and Pletscher 1996). The mean distance of a potential new colony to the nearest pond was 864 m, substantially less than the mean distance other studies on beaver dispersal have recorded.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This is not surprising as other studies in the native range found juveniles dispersed close to their natal colonies (Sun et al 2000;VanDeelen and Pletscher 1996). The mean distance of a potential new colony to the nearest pond was 864 m, substantially less than the mean distance other studies on beaver dispersal have recorded.…”
Section: Discussionsupporting
confidence: 72%
“…We followed a used-availability design in which all suitable parts of the landscape are assumed to be available to the individuals but some units are preferred over others. Beavers can travel long distances (we have recorded a 19 km dispersal event in this area using radio-telemetry) (see Leege 1968;Sun et al 2000;VanDeelen and Pletscher 1996), so they are likely to be able to sample all suitable units in the landscape. We decided to take all pixels occupied by watercourses in our study area as the landscape available to beavers.…”
Section: Resource Selection Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colonization process, which corresponds with beaver dispersal and settlement, has mostly been studied at the individual level using telemetry (Beer 1955;Leege 1968;Sun et al 2000;Campbell et al 2005;McNew and Woolf 2005). The data on beaver dispersal, however, were not sufficiently related to habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Although beavers mate with individuals other than their pair-bonded mate, extrapair mating is not restricted to mating within the colony; rather, numerous occurrences of intercolony extrapair mating have been observed (Crawford et al 2008). Despite reports of nearly equal dispersal rate and distance between the sexes (Bloomquist 2007;Havens 2006;McNew and Woolf 2005;Sun et al 2000), genetic kinship analysis has indicated female philopatry in colonies from 1 of our study populations (Crawford et al 2008). Such sex-biased philopatry can result in high genetic subdivision between breeding groups, because females within colonies will be more closely related to each other than they are to females from other colonies (Storz 1999).…”
mentioning
confidence: 99%